Quantitative studies on ferredoxin in greening bean leaves - Haslett, B. G. (1973)
Two methods of measuring small amounts of the iron–sulphur protein ferredoxin are described. One involves measurements of the signal at g=1.96 produced by reduced ferredoxin in an e.p.r. (electron-paramagnetic-resonance) spectrometer; the other depends on the rate of ferredoxin-dependent electron transport in a chloroplast bioassay measured in an O(2) electrode. These methods of measurement were used to examine the development of ferredoxin during the greening of etiolated bean leaves. Ferredoxin is present in low concentrations in the leaves and cotyledons of 14-day-old etiolated beans (Phaseolus vulgaris L. var. Canadian Wonder), and develops in a linear manner with time when the leaves are illuminated. This synthesis appears to be independent of chlorophyll synthesis during the early stages of greening. However, the chlorophyll/ferredoxin ratio reaches a final value of approx. 360 irrespective of the light intensity, indicating the existence of a control mechanism operative in deciding the stoicheiometry of these components in the mature chloroplast. The ferredoxin synthesis appears to be light-dependent, and red light is the most effective in its promotion. The effect of red illumination is not reversed by far-red light, indicating the absence of a phytochrome control of ferredoxin synthesis. From experiments using specific inhibitors of chloroplast protein synthesis, it is concluded that ferredoxin is synthesized on cytoplasmic ribosomes.